2018
DOI: 10.4103/jios.jios_116_17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Influence of Gingival Display on Smile Esthetics in Indian Females-A Computer-Aided Photographic Analysis

Abstract: Objectives:(1) To evaluate the influence of the amount of gingival display on smile esthetics and to compare the esthetic perception of six levels of gingival exposure (−3, −1, 0, +1, +3, +5 mm) between orthodontists, maxillofacial surgeons, dental students, and laypersons. (2) To evaluate the most acceptable level of gingival display during smile. Materials and Methods: Twelve adult females (20-30 years of age) were included in the study. A frontal intraoral and a frontal extraoral smile photograph were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In a study conducted by Sybaite et al 24 the effect of different amounts of gingival visibility (-6, -3, 0, 3, 6 mm) on smile aesthetics was investigated.Gingival visibility of 0 mm was aesthetically pleasing for all participants, while gingival visibility of 6 mm was not liked by any occupational groups. In a study by Maniyar et al 25 gingival visibility was changed as -3, -1, 0, 1, 3.5 mm, and 0 mm gingival visibility was accepted as more aesthetic by all participants.In our study, five photographs were created with different levels of gingival visibility, including 0 mm, 1 mm, 2 mm, 3 mm, and -1 mm (i.e., the gingival margins of the upper central incisors being covered by the upper lip line). As a result, gingival visibility of -1 mm was evaluated as being most aesthetic by all participants for both the male and female models, followed by gingival visibility of 0 mm.…”
Section: Discussionmentioning
confidence: 96%
“…In a study conducted by Sybaite et al 24 the effect of different amounts of gingival visibility (-6, -3, 0, 3, 6 mm) on smile aesthetics was investigated.Gingival visibility of 0 mm was aesthetically pleasing for all participants, while gingival visibility of 6 mm was not liked by any occupational groups. In a study by Maniyar et al 25 gingival visibility was changed as -3, -1, 0, 1, 3.5 mm, and 0 mm gingival visibility was accepted as more aesthetic by all participants.In our study, five photographs were created with different levels of gingival visibility, including 0 mm, 1 mm, 2 mm, 3 mm, and -1 mm (i.e., the gingival margins of the upper central incisors being covered by the upper lip line). As a result, gingival visibility of -1 mm was evaluated as being most aesthetic by all participants for both the male and female models, followed by gingival visibility of 0 mm.…”
Section: Discussionmentioning
confidence: 96%
“…Studies conducted in India reported the most aesthetic gingival display to be -2 mm 18 and 0 mm. 15 Subjects who were outside of the three main ethnic groups in Malaysia (Malay, Chinese and Indian) were classified into the "Others" category which consisted of a heterogeneous group of indigenous tribes in Malaysia, for example, Dayak, Iban, Kadazan and Orang Asli. People from the "Others" group favoured all smiles except gingival overexposure (+4 mm).…”
Section: Ethnicitymentioning
confidence: 99%
“…1,4,[7][8][9][10] To many, smiles with a gingival display of 0 to 2 mm are the most attractive. 8,[10][11][12][13][14][15] Nevertheless, recent studies from Asia have reported a gingival display of -2 mm to be the most attractive. 1,[16][17][18] Regarding the least aesthetic smile, many studies have found that a smile with an excessive gingival display of 3 mm or more, termed a 'gummy smile', to be the least attractive.…”
Section: Introductionmentioning
confidence: 99%